Human exposome assessment platform. Issue 6 (3rd December 2021) - Merino Martinez, Roxana; Müller, Heimo; Negru, Stefan; Ormenisan, Alex; Arroyo Mühr, Laila Sara; Zhang, Xinyue; Trier Møller, Frederik; Clements, Mark S.; Kozlakidis, Zisis; Pimenoff, Ville N.; Wilkowski, Bartlomiej; Boeckhout, Martin; et al.
Abstract : The Human Exposome Assessment Platform (HEAP) is a research resource for the integrated and efficient management and analysis of human exposome data. The project will provide the complete workflow for obtaining exposome actionable knowledge from population-based cohorts. HEAP is a state-of-the-science service composed of computational resources from partner institutions, accessed through a software framework that provides the world's fastest Hadoop platform for data warehousing and applied artificial intelligence (AI). The software, will provide a decision support system for researchers and policymakers. All the data managed and processed by HEAP, together with the analysis pipelines, will be available for future research. In addition, the platform enables adding new data and analysis pipelines. HEAP's final product can be deployed in multiple instances to create a network of shareable and reusable knowledge on the impact of exposures on public health.